2019
DOI: 10.1080/09513590.2019.1632088
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte quality in women with infertility associated endometriosis

Abstract: The mechanisms of endometriosis-related infertility remain still unknown. Endometriosis and clinical markers of oocyte quality are a very important problem of reproduction. The purpose of the study is to assess the quality of oocytes in women with infertility associated with endometriosis. The study included infertile reproductive aged women, between 29 and 40 years who underwent IVF and ICSI procedures. The patients were divided into three groups: group I involved 50 (n ¼ 50) patients with recurrent unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…This review showed that there a lower number of MII oocytes retrieved from women with endometriomas which is an agreements with other studies [ 23 , 35 ]. However, some studies showed no negative effect of an endometrioma on MII oocytes [ 34 , 58 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This review showed that there a lower number of MII oocytes retrieved from women with endometriomas which is an agreements with other studies [ 23 , 35 ]. However, some studies showed no negative effect of an endometrioma on MII oocytes [ 34 , 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…All eight studies [ 19 – 21 , 30 32 , 34 , 35 ] reported on the number of oocytes retrieved, which allowed quantitative pooled analysis. A significantly lower number of oocytes was retrieved from the endometrioma group relative to the control group (WMD-2.25; 95% CI 3.43 to − 1.06, p = 0.0002).…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 3 genes were enriched into the terms meiosis I and mitotic DNA replication. Endometriosis has a negative effect on oocyte quality and ovarian reserve, which may be the underlying cause of endometriosis-associated infertility (Orazov et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This original study was approved by the Institutional Review Board of the School of Medicine, Shandong University (No. 2019- [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In all, the records of 513 patients were collected, of whom 240 had achieved a live birth.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Some evidence indicates that ovarian surgery simply decreases the amount of viable ovarian tissue (6,7). Moreover, surgical manipulation might reduce the ovarian reserve, impede ovarian response, and possibly decrease the ART success rate (8)(9)(10). A systematic meta review of 13 studies has shown that surgical and expectant management of endometriomas prior to IVF yielded similar clinical pregnancy and live birth rates, antral follicle count (AFC), mature oocyte numbers, and miscarriage rates (11).…”
Section: Introductionmentioning
confidence: 99%